The Role of Visual Media in Supporting Elementary Students’ Learning Motivation: A Qualitative Study at SD Negeri 101883 PSR XIII Limau Manis Tanjung Morawa - Putri Danesa Malau; Gebyanna Paula Sinaga; Elsin Firma Situmorang; Roselli Kristanti Girsang; Maria Sihotang (Pustaka Karya Mandiri, 2026)
Visual media are important instructional tools that can help students understand learning materials more easily, maintain attention, and increase motivation during classroom learning. In elementary education, students often need concrete and visually meaningful learning experiences because abstract explanation alone may cause boredom, low participation, and difficulty in understanding concepts. This study aims to describe the role of visual media in supporting students’ learning motivation at SD Negeri 101883 PSR XIII Limau Manis Tanjung Morawa. This study employed a descriptive qualitative design. The participants were 20 third-grade students. Data were collected through classroom observation, interviews, documentation, and field notes during five learning meetings. The findings show that students responded positively to the use of visual media, including pictures, diagrams, graphics, videos, and visual presentations. Visual media helped students understand difficult concepts, increased attention, reduced boredom, improved classroom enthusiasm, and encouraged students to participate more actively in learning. Students also reported that visual materials made lessons easier to remember because they could directly see representations of the concepts being discussed. However, the findings also show that the effectiveness of visual media depends on teacher preparation, relevance of media to learning objectives, clarity of visual design, and the teacher’s ability to integrate visual media into classroom interaction. This study concludes that visual media can support students’ learning motivation when used meaningfully, contextually, and interactively.